2013
DOI: 10.1155/2013/412349
|View full text |Cite
|
Sign up to set email alerts
|

Economic Viability of Metallic Sodium-Cooled Fast Reactor Fuel in Korea

Abstract: This paper evaluates whether SFR metallic nuclear fuel can be economical. To make this determination, the cost of SFCF (SFR fuel cycle facilities) was estimated, and the break-even point of the manufacturing cost of SFR metallic nuclear fuel for direct disposal option was then calculated. As a result of the cost estimation, the levelized unit cost (LUC) for SFCF was calculated to be 5,311 $/kgHM, and the break-even point was calculated to be $5,267/kgHM. Therefore, the cost difference between LUC and the break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The PWR fuel dry transportation and storage cost for direct disposal can be calculated using Equation (18).…”
Section: Nuclear Fuel Cycle Cost Calculationmentioning
confidence: 99%
“…The PWR fuel dry transportation and storage cost for direct disposal can be calculated using Equation (18).…”
Section: Nuclear Fuel Cycle Cost Calculationmentioning
confidence: 99%
“…quantitative and economic studies have been reported on the back-end of fuel cycle options for Korea [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. However, most of the previous studies were conducted based upon the assumptions proposed by the investigators rather than upon the official national policy [6][7][8][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the previous studies were conducted based upon the assumptions proposed by the investigators rather than upon the official national policy [6][7][8][14][15][16]. In addition, neither detailed estimation of the total amount of SNF and TRUs in terms of radioactivity nor relative radiological toxicities of the SNF to be produced from all units of Korean NPPs have been openly reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Korea, which is one of Asia's advanced nuclear nations, operates a total of 23 nuclear power plant units (19 PWR (Pressurized Water Reactor) units and four CANDU (CANada Deuterium Uranium) units) [7]. However, the accumulated spent nuclear fuel inventory is an impediment to the continual nuclear power generation since temporary storage facilities for spent nuclear fuel used in a nuclear power generation plant will become saturated starting from 2024 [8].…”
Section: Introductionmentioning
confidence: 99%